Walking with gorillas : the journey of an African wildlife vet - Kalema-Zikusoka, Gladys (Arcade Publishing, 2023)
"Dr. Gladys Kalema-Zikusoka, Uganda's first wildlife veterinarian, tells the remarkable story of her life protecting critically endangered mountain gorillas. In the face of discrimination in a male-dominated world, one woman's passion and determination to build a brighter future offers inspiration and insights into what is truly possible for our planet when we come together. What begins as her enchanting account of being fresh out of vet school, treating sick gorillas, relocating wandering elephants, reintroducing giraffes, rescuing orphaned baby chimpanzees, and testing Cape buffalo for zoonotic diseases, beomes a tale of human health advocacy, as she realizes that in order to save wild animals from extinction, we must also help their human neighbors. When she makes the connection that diseases in the local human communities are affecting gorillas and tuberculosis is rampant in wild buffalo herds as well as among the villagers, she sets off on a parallel path creating a support system to improve health and well-being of the people surrounding Bwindi Impenetrable National Park. Thus, the NGO Conservation Through Public Health was born. Since those early days, Dr. Gladys has helped revolutionize conservation throughout the world with a focus on the integrated health of humans and wildlife. Walking with Gorillas is the story of her incredible journey." -- Book jacket.